K2-111: an old system with two planets in near-resonance. Issue 4 (27th October 2020) - Mortier, A; Zapatero Osorio, M R; Malavolta, L; Alibert, Y; Rice, K; Lillo-Box, J; Vanderburg, A; Oshagh, M; Buchhave, L; Adibekyan, V; Delgado Mena, E; Lopez-Morales, M; et al.
ABSTRACT: This paper reports on the detailed characterization of the K2-111 planetary system with K2, WASP, and ASAS-SN photometry, as well as high-resolution spectroscopic data from HARPS-N and ESPRESSO. The host, K2-111, is confirmed to be a mildly evolved (log  g = 4.17), iron-poor ([Fe/H] = −0.46), but alpha-enhanced ([α/Fe]=0.27), chromospherically quiet, very old thick disc G2 star. A global fit, performed by using PyORBIT, shows that the transiting planet, K2-111 b, orbits with a period Pb = 5.3518 ± 0.0004 d and has a planet radius of $1.82^{+0.11}_{-0.09}$  R⊕ and a mass of $5.29^{+0.76}_{-0.77}$  M⊕, resulting in a bulk density slightly lower than that of the Earth. The stellar chemical composition and the planet properties are consistent with K2-111 b being a terrestrial planet with an iron core mass fraction lower than the Earth. We announce the existence of a second signal in the radial velocity data that we attribute to a non-transiting planet, K2-111 c, with an orbital period of 15.6785 ± 0.0064 d, orbiting in near-3:1 mean motion resonance with the transiting planet, and a minimum planet mass of 11.3 ± 1.1 M⊕ . Both planet signals are independently detected in the HARPS-N and ESPRESSO data when fitted separately. There are potentially more planets in this resonant system, but more well-sampled data are required to confirm their presence and physical parameters.